Measuring the hardness via nanoindentation of a fiber-reinforced dental composite in the root canal - András Jakab; Kata Lilla Vánkay; Tamás Tarjányi; Gábor Gulyás; Krisztián Bali; Pál Patrik Dézsi; Márton Sámi; Márk Fráter (Hungarian Dental Association, 2024)
Introduction: Using short fiber-reinforced composite (SFRC) materials, individualized root posts can be fabricated to reinforce root canal treated teeth (Bioblock technique). The question regarding this technique is the efficiency of SFRC polymerization in different depths of the root canals. Additionally, whether the polymerization of SFRC could be improved with light transmission methods remains a question to be answered. Materials and methods: 20 plastic teeth (4 groups, n = 5/group) simulating root canal treatments were used for this research, which). All teeth were restored with SFRC material, starting from 6 mm deep in the root canal till the orifice. In group 1 and 3, the root canal was filled with SFRC material in layers, while in groups 2 and 4, it was filled in a bulkfill manner. In group 1 and 3, the SFRC material was light cured through a fiberglass post, whereas in group 2 and 4, a modified light source was utilized. After embedding and sectioning the samples hardness of the SFRC material at 2 mm intervals in the root canal were measured (1st, 2nd and 3rd layer, from apical to coronal direction). Results: For the 1st layer, light curing through the fiberglass post (group 3) resulted in significantly higher hardness compared to the modified light conductor (group 4) in the bulk-fill application method. In the 2nd layer, both group 1 and 3 showed significantly higher hardness compared to group 4. Conclusion: Illumination through a fiberglass post provides outstanding hardness for SFRC material in bulk-fill application in the apical and middle layers.